2016
DOI: 10.4103/0974-777x.193749
|View full text |Cite
|
Sign up to set email alerts
|

Consensus recommendation for India and Bangladesh for the use of pneumococcal vaccine in mass gatherings with special reference to Hajj pilgrims

Abstract: Respiratory tract infections are prevalent among Hajj pilgrims with pneumonia being a leading cause of hospitalization. Streptococcus pneumoniae is a common pathogen isolated from patients with pneumonia and respiratory tract infections during Hajj. There is a significant burden of pneumococcal disease in India, which can be prevented. Guidelines for preventive measures and adult immunization have been published in India, but the implementation of the guidelines is low. Data from Bangladesh are available about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…4,5 Bangladesh does not have a national influenza immunisation policy and vaccine uptake remains low; 6 however, vaccine campaigns have been recommended for specific high-risk subgroups including Hajj pilgrims. 7 Previous studies have reported a distinct seasonal influenza pattern in Bangladesh, 8,9 but long-term trends and subnational heterogeneity in seasonality have not been examined. A better understanding of regional influenza transmission patterns in Bangladesh could be used to bolster the development of immunisation policies, direct appropriate health resource planning and facility preparedness, and support diagnostic and treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Bangladesh does not have a national influenza immunisation policy and vaccine uptake remains low; 6 however, vaccine campaigns have been recommended for specific high-risk subgroups including Hajj pilgrims. 7 Previous studies have reported a distinct seasonal influenza pattern in Bangladesh, 8,9 but long-term trends and subnational heterogeneity in seasonality have not been examined. A better understanding of regional influenza transmission patterns in Bangladesh could be used to bolster the development of immunisation policies, direct appropriate health resource planning and facility preparedness, and support diagnostic and treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The consensus guidelines for India and Bangladesh for the use of pneumococcal vaccine in mass gatherings and for Hajj pilgrims recommend ( “Grants—Immunization Programme,” 2018 ; Mathai et al, 2016 )…”
Section: Resultsmentioning
confidence: 99%
“…Currently, pneumococcal vaccination is not one of the officially recommended/compulsory vaccinations in the Hajj health requirements set by the Saudi authorities (Saudi Ministry of Health, 2017). Although some countries have recommended pneumococcal vaccination for their Hajj pilgrims (Feldman et al, 2013;Mathai et al, 2016;Rashid et al, 2013), an evidence-based policy requires a better understanding of the clinical and economic burden of the disease associated with Hajj. This study is a first step in providing such data, by defining the burden of the disease in the Hajj season using a more reliable diagnostic test for pneumococcal pneumonia.…”
Section: Discussionmentioning
confidence: 99%